Continuous IEQ monitoring system: Performance specifications and thermal comfort classification. (February 2019) - Parkinson, Thomas; Parkinson, Alex; de Dear, Richard
Abstract: The quality of buildings can be assessed in terms of the indoor air quality, thermal comfort, lighting quality, acoustic comfort afforded the occupants, collectively referred to as Indoor Environmental Quality (IEQ). A major barrier to a more thoroughly representative audit of actual IEQ performance are the expense and complexity of the measurement instrumentation required. Rapid developments in sensor technology in recent years present the opportunity for continuous and pervasive IEQ monitoring to deliver truly representative characterisations of building performance at a modest cost. The last remaining obstacle to realising these developments seems to be a concern about instrument accuracy. In this paper we test the performance of a low-cost IEQ monitoring system (SAMBA) introduced in an earlier paper. Calibration data from 100 devices was analysed to calculate the standard error of the estimate as a measure of equipment accuracy. Those performance specifications were used in a Monte Carlo simulation based on measurements of thermal comfort parameters from 24 office buildings. Performance measures suggests the low-cost system, whilst not as accurate as laboratory equipment, is more than sufficient for building IEQ diagnostics and compliance assessments. Furthermore, the results of the Monte Carlo simulation show that continuous monitoring systems are better at characterising long-term performance than ad hoc measurement strategies using precision equipment. Low-cost pervasive monitoring technologies therefore offer a unique opportunity to improve our quantitative understanding of, and response to, indoor environmental quality issues. Highlights: Reviews standards for instrument specifications and IEQ measurement protocols. Evaluates the performance of 100 low-cost continuous IEQ monitoring systems. Monte Carlo methods test the performance of different sensors for continuous monitoring. Show continuous monitoring is better than spot measurements for long-term comfort assessments.